ANALISIS DAN PERANCANGAN SISTEM INFORMASI APLIKASI AKADEMIK (SISKA) BERBASIS EPSBED DI LINGKUP STMIK INSAN PEMBANGUNAN (Analysis and Design of Academic Information Systems (SISKA) Based on EPSBED of STMIK Insan Pembangunan Bitung – Tangerang) - Nurasiah . (Insan Pembangunan Sistem Informasi dan Komputer (IPSIKOM), 2013)
ABSTRACTThis report presents an analysis and design of academic information systems based on STMIK Insan Pembangunan EPSBED. Problems that occur on campus STMIK Insan Pembangunan is an academic system that has not been integrated with the report EPSBED so often happens when a data validation to invalid data, data search difficulty, for making the report because the data are not yet available, as well as data storage is not supported, so that reporting EPSBED the pass / not in accordance with the schedule specified. With the establishment of this academic system will minimize the problem and reporting it to run smoothly. Designing a computerized information system and this will be based EPSBED ensure accuracy and time to generate information in order to be able to control the reporting schedule set by Kopertis IV. Observations and research on STMIK Insan Pembangunan has produced a design of Academic Information Systems (SISKA) based EPSBED. Academic Information System has been implemented so that the problems that exist in STMIK Insan Pembangunan can be completed.